Jerusalem in history - ʿAsalī, Kāmil Ǧamīl al- (Scorpion Publishing Ltd, 1989)
Klappentext: The city of Jerusalem has a special place in the consciousness of the great monotheistic religions. Throughout its history it has been the site of glories and catastrophes; a place that has been witness to transition and occupation by a diversity of peoples and an object of pilgrimage through the centuries. This important work begins to provide a comprehensive outline of the amazing history of the city. It moves from the Bronze Age to the tensions of present-day Jerusalem and presents a balanced and authentic picture, that helps to correct the often distorted images of the city presented over the last fifty years. Kamil J. Asali is the author of fifteen books on the Islamic heritage of Jerusalem. He received his PhD in philosophy from the University of Humboldt in Berlin. Rashid Khalidi is Professor of Middle East History and Director of the Center for International Studies at the University of Chicago.